Enhancement of the Fillrate orders ratio by a planning and control model under the PDCA approach in the printing sector - Polo-Camarena, Piero; Real-Dueñas, Jesus; Quiroz Flores, Juan Carlos; Ali, Ahad (LACCEI, 2023)
The small business non-primary manufacturing sector has grown significantly each year. However, its growth is diminished by the problems that impact the fulfillment of orders, which represent a billing that has yet to be received for this sector. In this aspect, small companies in this area seek to have a greater fulfillment of orders in quantities to increase customer satisfaction and reduce losses. In the following research work, the low fill rate represents the main problem that generates economic losses for a small company in the printing manufacturing sector. Therefore, implementing a production planning and control model is proposed under the PDCA methodology using tools such as forecasts, MPS, MRP, and 5S to increase the fill rate in the company. This research contemplates an analysis of the production and storage planning process, where the main root causes of the problem are diagnosed to attack them with Production planning and control tools. Finally, the proposed model achieves a fill rate increase of 16.50% in the quantities of purchase orders dispatched.